Hubungan Kematangan Emosi dengan Empati pada Bystander Cyberbullying - Amanah, Wulan Aldira Rabiatul; Winata, Efan Yudha; Aisyah Putri Rawe Mahardika (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to determine the relationship between emotional maturity and empathy in cyberbullying bystanders. This research method uses quantitative research methods with a correlational type. The sample for this research consisted of 86 students at the Sumbawa University of Technology. The sampling technique uses purposive sampling. The data in this research were obtained from research instruments in the form of an emotional maturity scale and an empathy scale. The scale used consists of 25 items and 18 items. The statistical method in this research uses the Pearson product moment correlation analysis technique. Based on the data analysis carried out, it is known that there is a relationship between emotional maturity and empathy. This is known from the significance value of p = 0.03 or p < 0.05 and the correlation coefficient value of r = 0.317 which is included in the weak category and shows that there is a positive relationship between emotional maturity and empathy in cyberbullying bystanders, both variables are positive variables or two variables that do not oppose each other. This means that the higher the emotional maturity, the higher the empathy and the lower the emotional maturity, the lower the empathy